Impact of extraction methods on the properties of Carica papaya pseudostem fibers from Cameroon used as reinforcement in biocomposites - Jean Aimé Mono; Sandrine Emvoutou Ndongo; Odette Thérèse Adegono Assiene; Armel Mewoli; Rachelle Appolince Nguefack Assona; Richard Hervé Bitete; Giresse Ulrich Defo Tatchum; Claude Takoumbe (Heliyon)
Carica papaya pseudostems are widely available as biomass waste in Cameroon. These agricultural wastes can be effectively used as natural fibers in the manufacture of biocomposites. In this study, Carica papaya fibers were extracted from papaya pseudostems by retting with water and an alkaline sodium hydroxide (NaOH) solution at different concentrations (2.5 %, 5 %, and 7.5 %). An experimental campaign is being conducted on the physical, chemical, thermal, mechanical, and morphological characteristics of Carica papaya fibers. Fourier transform infrared spectroscopy (FTIR) of Carica papaya fibers extracted by water retting and those extracted with NaOH indicates that the cellulose, hemicellulose, and lignin functional groups are present in the fibers and are dissolved considerably as the percentage of NaOH increases. Scanning electron microscopy (SEM) in the longitudinal plane gives a visual representation of the rough and irregular surfaces without the presence of impurities on the chemically extracted fibers compared to that extracted with water. In contrast to the decrease in diameter, the measured density of Carica papaya pseudostem fibers increased with NaOH concentration (0.633 –1.522 g cm−3), all of which remained light fibers. Water absorption decreased from 159.36 % to 141.28 % with increasing NaOH, and relative humidity dropped to 6.41 %. The thermal stability of Carica papaya fibers extracted at concentrations of 2.5 % NaOH (215 °C), 5 % NaOH (200 °C), and 7.5 % NaOH (175 °C) showed a clear decrease compared to those extracted by water retting (220 °C). Fibers extracted at 2.5 % NaOH achieved a tensile strength of 287.55 ± 56 MPa, a tensile modulus of 8.271a± 1.62, and 3.505 ± 1.01 % elongation. The tensile properties of these fibers showed great variability, and an influence of diameter was observed, indicating the need to study the influence of technique and NaOH mass concentration. The results show that Carica papaya fiber extracted at a concentration of 2.5 % will be the most suitable for biocomposite applications.